miR-494 Contributes to Estrogen Protection of Cardiomyocytes Against Oxidative Stress via Targeting (NF-κB) Repressing Factor - Tang, Zhi-Ping; Zhao, Wei; Du, Jian-kui; Ni, Xin; Zhu, Xiao-Yan; Lu, Jian-Qiang (Frontiers in Endocrinology, 2018)
Oxidative stress plays a pivotal role in the initiation and progression of cardiac diseases. Estrogens have been demonstrated to exert pleiotropic cardioprotective effects, among which anti-oxidative stress is one of the key effects linking estrogens to cardioprotection. By using a microRNAs (miRs) microarray screening approach, we discovered an increase in miR-494, which is known to exert cardioprotective effects, in estrogen-treated cardiomyocytes. We hypothesized that the upregulation of miR-494 might contribute to estrogen-mediated cardioprotection against oxidative stress. We found that E2 stimulates miR-494 expression via ERα in both cardiomyocytes and the myocardium of female mice. The miR-494 inhibitor attenuated the protective effect of 17beta-estradiol (E2) against oxidative stress-induced injury in cardiomyocytes. By contrast, the miR-494 mimic protected cardiomyocytes against oxidative stress-induced cardiomyocyte injury. Using real-time PCR, western blot and dual-luciferase reporter gene analyses, we identiﬁed nuclear factor kappa B (NF-κB) repressing factor (NKRF) as the miR-494 target in cardiomyocytes. E2 was found to inhibit NKRF, thus activating NF-κB through a miR494-dependent mechanism. In addition, the protective effects of E2 and miR-494 against oxidative stress in cardiomyocytes were eliminated by the NF-κB inhibitor. In summary, this study demonstrates for the first time that estrogen inhibits NKRF expression through ERα-mediated upregulation of miR-494 in cardiomyocytes, leading to the activation of NF-κB, which in turn results in an increase in antioxidative defense. ERα-mediated upregulation of miR-494 may contribute to estrogen protection of cardiomyocytes against oxidative stress.